Assessing the Potential of Innovation as a Generator of Change - Fernández-Maqueira, María José; Blanco-Encomienda, Francisco Javier; Latorre-Medina, María José (Opción, 2016)
In recent years many efforts have been made aiming to improve the situation of educational quality. Several plans to improve the quality of teaching have been implemented with skepticism and reluctance. Unfortunately, these well-intentioned reforms have not led to the expected goal. In this paper we analyze the two key elements of an education system: educational centers and teachers. Thus, we first describe some problems that are bounded to the management of the centers and then we define the teacher profile demanded by classrooms: the innovative teacher as a facilitator of learning and change.